CURCUMIN AND ITS NANOFORMULATIONS: A COMPREHENSIVE OVERVIEW FOR THE MANAGEMENT OF DIABETES COMPLICATIONS - NATH, JUNMONI; KALITA, BHUPEN; DAS, GOURANGA (International Journal of Current Pharmaceutical Research, 2019)
Diabetes is a chronic metabolic disorder that has reached pandemic proportions, and which is a major cause of morbidity and mortality worldwide. Type 1 diabetes is an autoimmune disorder resulting in almost complete destruction (98%) of insulin secreting beta cells in the pancreas, while type 2 diabetes is considered to be a disease of protein misfolding where, in addition to the average 65% loss of beta cell mass, insulin resistance occurs in target organs. Diabetic complications, such as retinopathy, nephropathy, neuropathy and cardiovascular disease, are common and majorly impact a patient’s quality of life. Curcumin is the yellowish polyphenolic component of the dietary spice turmeric, which is the rhizomes of Curcuma longa, a herb in the ginger family (Zingiberaceae). Curcumin effectively reduces glycemia and hyperlipidemia but also has beneficial effects on diabetic complications due to its anti-inflammatory and antioxidant properties, in a relatively inexpensive and safe manner. New improved methods of delivering curcumin are being developed including nanoparticles and lipid/liposome formulations that increases its absorption and bioavailability as curcumin is poorly absorbed by the digestive system and undergoes glucuronidation and excretion rather than being released into the serum and systemically distributed. Development and refinement of these technologies will enable cell-directed targeting of curcumin and improved therapeutic outcome. The current review focuses on the antidiabetic efficacy of curcumin and nano-drug delivery approaches in attenuating diabetes and its complications.